Validation of Mathematics Test to Assess Polytechnic Students' Problem Solving - Shida, Nurul; Abdullah, Abdul Halim; Osman, Sharifah; Ismail, Norulhuda (Mathematics Education Journal, 2023)
Mathematics education and problem-solving are inseparable due to the significance of solving problems with educational implications. This study aims to describe the process of developing and validating a test that measures problem-solving skills in Integral Calculus. This study is done to identify traces of the intended strategy in the answers, style, and quality of the student's responses. Data collection techniques were carried out through mathematical tests using problem-solving questions. The difficulty index, discrimination index, and reliability were calculated to analyze the data for each problem-solving instrument. Based on expert reviews, evaluations, and data analysis tests, five valid problem-solving instrument items with a discrimination index greater than 0.30 and Cronbach's alpha reliability greater than 0.60 have been developed. Therefore, it can be concluded that the developed maths test questions can enhance the problem-solving skills of Ibrahim Sultan Polytechnic students. DOI: https://doi.org/10.22342/jpm.17.2.20171.265-278